Pembuatan asam sulfat dari belerang dengan katalisator asam nitrat dalam satu langkah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT In order to get simpler, cheaper, and more concentrated sulfuric acid production, several experimental investigations have been done, and one of them combined the sulfur dioxide oxidation and the gas absorption in one reactor, so that the sulfuric acid production was carried out in two steps at atmosferic pressure. Another shortest step could improve the existing process. This work investigated sulfuric acid production from sulfur in one step in one reactor, using nitric acid as catalyst. Within the range of allowable pressure and temperature of 2 - 5 atm and 125° C - 145° C, respectively, a maximum conversion of 79,59 %, was achieved in 60 minute reaction time, with 56 % nitric acid concentration and 145°C. The correlation between sulfur conversion and reaction time, showed a pseudo first order reaction. The reaction rate constant was in conformity with Arrhenius equation with a frequency factor of 1.86 106 men"' and an activation energy of 22592,19 cal/gmol. Nitric acid concentration affected the rate constant logarithmically. The correlation between reaction rate constant, nitric acid concentration, and temperature could be expressed as k = 1.947 (1010) CI 0970 exp (-11,156.25/T) with an average standard deviation of 12.26 %.